Modified Synchronous Reference Frame Based Harmonic Extraction for Shunt Active Filter - C.S. Subash Kumar; V. Gopalakrishnan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents the modified synchronous reference frame based Shunt Active Filter (SAF) for the instantaneous compensation of harmonic current present at the Point of Common Coupling. The harmonics generated by the non linear load are extracted using the positive frame and negative frame of the input signal using the modified synchronous reference frame theory with extended Multiple Reference Frame based PLL (EMRFPLL). Based on the harmonics extracted, pulse width modulation signals are generated using Artificial Neural Network based Space Vector Pulse width Modulation technique (ANNSVPWM). Using this switching technique the losses can be reduced and compensation can be done more accurately The concept was verified using MATLAB / Simulink Simulation and the results confirm the THD at point of common coupling is below the required standards.